2016
DOI: 10.1177/1941738116654863
|View full text |Cite
|
Sign up to set email alerts
|

Elbow Biomechanics of Pitching

Abstract: Background:Elbow pain and elbow injuries are common in youth baseball players. It is not clear whether pitching experience and/or age creates biomechanical differences at the elbow and whether these differences place an athlete at greater risk.Hypotheses:(1) Youth pitchers will have differing elbow kinematics with regard to flexion/extension, internal/external rotation, and pronation/supination when compared with nonbaseball athletes and (2) younger youth pitchers will have differing elbow kinematics when comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Our initial focus in gaining an understanding of youth baseball player shoulder function was to examine the changes in isokinetic shoulder joint torque and power throughout the majority of the baseball season in conjunction with shoulder complex training via Crossover Symmetry. It has been shown that an increased volume of throwing due to extended playing seasons have led to an increase in throwing-related shoulder and elbow injuries (Hadro et al, 2019). Thus, understanding changes in shoulder complex function during a playing season and the potential impact of a sustainable shoulder-training program is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Our initial focus in gaining an understanding of youth baseball player shoulder function was to examine the changes in isokinetic shoulder joint torque and power throughout the majority of the baseball season in conjunction with shoulder complex training via Crossover Symmetry. It has been shown that an increased volume of throwing due to extended playing seasons have led to an increase in throwing-related shoulder and elbow injuries (Hadro et al, 2019). Thus, understanding changes in shoulder complex function during a playing season and the potential impact of a sustainable shoulder-training program is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…11 This phase occurs just prior to front foot plant and is associated with elbow flexion angles ranging from 60° to 90°. 10,19…”
Section: Discussionmentioning
confidence: 99%
“…At this time, the muscles of the lower limbs need strong muscle strength and power that can be converted into breaking force and push-off force of each body segment while minimizing the loss of ground reaction force (Campbell et al, 2010;Kageyama et al, 2014). As previously described, the knee flexion angle of the stepping foot plays an important role in this process, with an ideal flexion angle of 40°-49° (Fehr et al, 2016).…”
Section: Knee Joint Injurymentioning
confidence: 99%
“…This is caused by impingement of the supraspinatus tendon as the gap between the subacromial part and greater humerus joint is narrowed when the arm is lifted excessively and rotated internally (Burkhart et al, 2000;Wu et al, 2022). Accordingly, the clinical guide on analysis of pitching motion reported that when the shoulder rotates externally at the BR event, the shoulder abduction angle must secure mobility of 70-94° (Diffendaffer et al, 2022;Fehr et al, 2016). This suggests that when the arm is raised higher than the shoulder during rotational movement of the shoulder, the pressure applied to the supraspinatus tendon increases, and subsequently, the risk of impingement syndrome increases.…”
Section: Shoulder Joint Injurymentioning
confidence: 99%